Screening for atrial fibrillation – a cross-sectional survey of healthcare professionals in primary care - Taggar, Jaspal; Coleman, Tim; Lewis, Sarah; Jones, Matthew (Public Library of Science, 2016)
Introduction: Screening for atrial fibrillation (AF) in primary care has been recommended; however, the views of healthcare professionals (HCPs) are not known. This study aimed to determine the opinions of HCP about the feasibility of implementing screening within a primary care setting.